A detailed analysis of the determination of fracture toughness by nanoindentation induced radial cracks. Issue 2 (February 2020) - Guo, Yuning; Staedler, Thorsten; Müller, Julian; Heuser, Steffen; Butz, Benjamin; Jiang, Xin
Abstract: The correlation between the choice of reference material and model utilized in determining fracture toughness from indentation-induced radial cracks was critically investigated with six commonly used reference materials. Initially, the empirical constants in Anstis's and Laugier's equations were calculated, compared and analyzed. According to the values of the constants, the reference materials were categorized into three groups. This classification was further verified by evaluating the corresponding constants of 13 additional equations. To account for the classification, FIB technique was employed to examine the crack morphology in the reference materials – Si (100) features an almost Half-penny-shaped crack while the cracks in SiC (0001) display nearly as a rectangle, both far from the assumptions employed by the models. Subsequently, an improved and more reliable procedure to determine fracture toughness is proposed. Finally, with this procedure, the fracture toughness of a diamond/SiC composite film is determined to be 11.1 ± 1.1 MPa m 1/2 .